2021
DOI: 10.1136/tsaco-2020-000636
|View full text |Cite
|
Sign up to set email alerts
|

Development of a large animal model of lethal polytrauma and intra-abdominal sepsis with bacteremia

Abstract: BackgroundTrauma and sepsis are individually two of the leading causes of death worldwide. When combined, the mortality is greater than 50%. Thus, it is imperative to have a reproducible and reliable animal model to study the effects of polytrauma and sepsis and test novel treatment options. Porcine models are more translatable to humans than rodent models due to the similarities in anatomy and physiological response. We embarked on a study to develop a reproducible model of lethal polytrauma and intra-abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cho et al 24 also showed increasing PT and declining MA in their multicenter polytrauma swine model; however, their use of normal saline (NS) creates a dilutional coagulopathy. Other previous military-relevant polytrauma models utilized NS; 23,25 however, we avoided NS to prevent dilutional coagulopathy and instead evaluate iatrogenic TIC. Thus, the increasing PT and decreasing MA levels are significantly correlated with greater blood loss and deeper shock leading to TIC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cho et al 24 also showed increasing PT and declining MA in their multicenter polytrauma swine model; however, their use of normal saline (NS) creates a dilutional coagulopathy. Other previous military-relevant polytrauma models utilized NS; 23,25 however, we avoided NS to prevent dilutional coagulopathy and instead evaluate iatrogenic TIC. Thus, the increasing PT and decreasing MA levels are significantly correlated with greater blood loss and deeper shock leading to TIC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described military relevant polytrauma models include a noncompressible torso hemorrhage model, 23 a multicenter lethal triad model (consisting of acidosis, hypothermia, and dilutional coagulopathy), 24 and an intra-abdominal sepsis model incorporating TBI. 25 Our newly created model focuses on DCBI with TBI, TI, and HS; thus incorporating additional challenges that TBI contributes to shock resuscitation and vice versa. Secondary insults such as hypotension, hypoxia, and inflammation lead to additional neurological injury and worsen secondary Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice underwent a 1 inch long midline laparotomy with bilateral abdominal rectus muscle crush injury. After entry to the abdomen was achieved bilateral hemostat clamps were placed onto the abdominal rectus muscles for 30 s. Methods utilized here were adapted from those previously described in a porcine model (21,22). After laparotomy and crush the abdomen was closed and animals were recovered in warmed recovery area.…”
Section: Laparotomy and Abdominal Wall Crushmentioning
confidence: 99%